2014
DOI: 10.1097/igc.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbogen Breathing and Nicotinamide Added to Standard (Chemo)Radiation Treatment of Advanced Cervical Cancer in Indonesia

Abstract: Addition of CON to standard (chemo)radiation gives comparable survival and control rates. The effect of CON might be underestimated due to differences in baseline characteristics. Because chemotherapy cannot always be (completely) administered in low-resource settings, CON could be a worthy substitute. The CON treatment is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Our study showed a significantly higher tumor volume shrinkage in the treatment group without additional toxicity. Subjects were comfortable after underwent chemoradiotherapy with additional carbogen, as also shown in several previous studies (20,24).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our study showed a significantly higher tumor volume shrinkage in the treatment group without additional toxicity. Subjects were comfortable after underwent chemoradiotherapy with additional carbogen, as also shown in several previous studies (20,24).…”
Section: Discussionsupporting
confidence: 77%
“…The addition of carbogen and nicotinamide in radiotherapy showed the improvement of the treatment response, especially in patients that have a contraindication for chemotherapy. Therapy with carbogen and nicotinamide was safe, although, some patients exhibited the nicotinamide intolerance (10,19,20). Nausea and vomiting appeared in patients who underwent head and neck radiation in conjunction with nicotinamide (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiosensitizer is a compound which, when combined with radiation, will provide greater tumour inactivation than the additive effect of each modality. 3,4 The majority of radiosensitizers are synthetic chemical compounds, which have been proven to be too toxic in effective clinical doses. Radiosensitizer made of natural materials is believed to be safer than synthetic materials.…”
Section: Introductionmentioning
confidence: 99%